Distribution of somatostatin-immunoreactive nerve fibres in Peyer's patches. Issue 9 (September 1992) - Fehér, E; Fodor, M; Burnstock, G
Abstract : The distribution of somatostatin-immunoreactive nerve fibres in Peyer's patches of the cat was demonstrated by immunocytochemical techniques. A large number of immunoreactive nerve fibres was observed in the tela submucosa very close to the Peyer's patches. Some immunoreactive nerve cell bodies were also found in this layer. The immunoreactive nerve terminals ran around the margin of the follicles and only a few nerve fibres were observed in the centre of follicles. Electron-microscopic investigation showed that these immunoreactive nerve terminals were in very close contact with lymphocytes and plasma cells, where no Schwann cell sheath was interposed. The gap between the nerve processes and the lymphocytes and plasma cells was about 20-200 nm, and occasionally less. These results provide morphological evidence consistent with the view that somatostatin has a neuroimmunomodulatory action.